Embryology - Dudek, Ronald W. (New York Wolters Kluwer, 2008)
"The sixth edition of BRS Embryology includes improvements based on suggestions and comments from the many medical students who have used this book in preparation for the USMLE Step 1 examination and those students who have reviewed the book. I pay close attention to these suggestions and comments in order to improve the quality of this book. The goal of BRS Embryology is to provide an accurate and quick review of important clinical aspects of embryology for the future physician"
Include Illustration and Index
Keywords: Embryology, Human -- Embryology